2001
DOI: 10.1016/s0896-6273(01)00410-x
|View full text |Cite
|
Sign up to set email alerts
|

Axo-Axonal Coupling

Abstract: We provide physiological, pharmacological, and structural evidence that axons of hippocampal principal cells are electrically coupled, with prepotentials or spikelets forming the physiological substrate of electrical coupling as observed in cell somata. Antidromic activation of neighboring axons induced somatic spikelet potentials in neurons of CA3, CA1, and dentate gyrus areas of rat hippocampal slices. Somatic invasion by these spikelets was dependent on the activation of fast Na(+) channels in the postjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
103
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 399 publications
(114 citation statements)
references
References 53 publications
(3 reference statements)
10
103
1
Order By: Relevance
“…The reduction in gamma power by the gap-junction blocking agent carbenoxolone suggested that the axons of layer II͞III are electrically coupled, as appears to be the case for pyramidal neurons in hippocampus (27,32). Finally, although not a comprehensive computational model of neocortical networks as yet, the model predicted accurately the physiological and pharmacological experimental data presented, and suggested that RS neurons and FRB neurons are electrically interconnected, and that such interconnections are critical for persistent neocortical gamma oscillations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The reduction in gamma power by the gap-junction blocking agent carbenoxolone suggested that the axons of layer II͞III are electrically coupled, as appears to be the case for pyramidal neurons in hippocampus (27,32). Finally, although not a comprehensive computational model of neocortical networks as yet, the model predicted accurately the physiological and pharmacological experimental data presented, and suggested that RS neurons and FRB neurons are electrically interconnected, and that such interconnections are critical for persistent neocortical gamma oscillations.…”
Section: Discussionmentioning
confidence: 84%
“…In the model, RS spikelets occurred on average at 2.2 Hz (12 cells) and corresponded to axonal spikes that conducted antidromically with decrement (ref. 27 and Fig. 2 A), whereas axonal spikes in FRB cells mainly led to full spikes or multiplets, presumably because of the relative depolarization and altered intrinsic currents in FRB cells.…”
Section: Resultsmentioning
confidence: 95%
“…The model simulations predicted that, if ectopic spikes provided the main driving force for the generation of the rhythm, then conduction of these spikes through gap junctions forming an axonal plexus would be a critical component of the mechanism. Dye coupling within layer V neuron populations has been observed in adult cortex (22) and the huge incidence of spikelets, associated with axo-axonic dye coupling and gap junctional communication in hippocampus (23)(24), suggested such a mechanism possibly may underlie the beta2 rhythm. Both octanol (1 mM, data not shown) and carbenoxolone (0.2 mM, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, layer V neurons form a major input pathway to basal ganglia, which also demonstrate beta rhythms (10). Here, we demonstrate an in vitro model that shows that a beta2 rhythm (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) can be specifically generated in layer V of neocortex in a manner independent of gamma rhythmogenesis and of glutamatergic synaptic excitation. Beta2 generation in layer V stands in contrast to cortical gamma rhythms that have been shown to originate in layers II͞III in in vitro models (11) and may underlie cortico-cortical synchronization (12).…”
mentioning
confidence: 76%
See 1 more Smart Citation